Aplikasi M-Commerce Berbasis Android Pada Toko “Fani Bags” - Azran Budi Arief (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2014)
Bags Fani store is one bag shop. Fani Bags store sells a wide range of bags such as backpacks, travel bags, briefcases etc. However, the mechanism of buying and selling or marketing is done manually, the buyer must come to the store to buy goods from Fani Bags. Then it becomes inefficient. M-commerce (mobile commerce) is a trading system that is performed by the method of trading is done with portable media or mobile devices such as smartphones, PDAs etc. This application is based Mobile Application (Android) using java programming and MySQL as the database and PHP as webserver. M-commerce to be a solution to solve the problems on the Fani Bags store due to m-commerce and smart phones as a media liaison, customers can easily access or purchase products Fani Bags store without having to come to the store. It can be concluded using mobile commerce applications of this transaction will be carried out more easily, efficiently, and of course the wider area coverage